2011
DOI: 10.1029/2010ja015627
|View full text |Cite
|
Sign up to set email alerts
|

Shock-driven variation in ionospheric outflow during the 11 October 2001 moderate storm

Abstract: [1] The Composition and Distribution Function (CODIF) Analyzer on board the Cluster spacecraft frequently observes narrow-energy, field-aligned O + ions over the polar caps and in the lobes, particularly during storm times. This population is due to ion outflow from the cusp. During the 11 October 2001 moderate storm, CODIF, located in the southern lobe at ∼12 Earth radii (R E ) down the tail and moving inbound, observed a change in the outflow. A sudden increase in solar wind dynamic pressure at 1702 UT led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…[22] We have analyzed the Cluster and MEX observations before and during a CIR passage. The O + outflow observed above Earth's polar region was consistent with a cusp origin scenario [e.g., Nilsson et al, 2004;Kistler et al, 2010a;Zhang et al, 2011]. The statistical studies revealed that the outflow rate from the cusp is sensitive to solar wind kinetic energy [Moore and Horwitz, 2007] but not related to geomagnetic activity level [Yau and Andre, 1997].…”
Section: O + Outflow On Marssupporting
confidence: 61%
“…[22] We have analyzed the Cluster and MEX observations before and during a CIR passage. The O + outflow observed above Earth's polar region was consistent with a cusp origin scenario [e.g., Nilsson et al, 2004;Kistler et al, 2010a;Zhang et al, 2011]. The statistical studies revealed that the outflow rate from the cusp is sensitive to solar wind kinetic energy [Moore and Horwitz, 2007] but not related to geomagnetic activity level [Yau and Andre, 1997].…”
Section: O + Outflow On Marssupporting
confidence: 61%
“…Thus it seems that the high altitude cusp provides a likely source for the deep-tail beams. The high energy O + (∼10 keV) beams are also occasionally observed by Cluster in the near-Earth (<19 R E ) lobe when a shock compresses the magnetosphere (Zhang et al 2011b), bringing in the populations that are close to the magnetopause.…”
Section: O + Acceleration In the Lobesmentioning
confidence: 84%
“…Cladis et al [2000] showed an example in which the centrifugal acceleration from a sudden compression during a storm increased the O + parallel velocity by~500 eV. Zhang et al [2011] studied a case where a large change in the energy of O + was observed when there was a sharp increase in solar wind pressure and tested whether this was due to centrifugal acceleration. They found that the observed energy increase in the lobe O + beam is more likely due to field line displacement and the velocity filter effect and not due to centrifugal acceleration.…”
Section: Introductionmentioning
confidence: 99%